Surface Improvement on Low Carbon Steel with Gas-carbonitriding Hardening Process as an Alternative Material used in Producing Blade for Organic Fertilizer Grinder - Takunsaranakom, Chanyut (Princess of Naradhiwas University Journal, 2021)
The research objective was to study the method of applying gas-carbonitriding hardening process to improve the mechanical properties of AISI 1020 low carbon steel for using as a production material for producing blade for organic fertilizer grinder. The mechanical properties of agricultural equipment were examined, and the equipment was applied with a gas-carbon nitriding hardening method to increase wear resistance of the impact blades. The testing process was done with 21 pieces of blade as follows: (1) 7 pieces of non-hardened blades, (2) 7 pieces of gas-carbonitriding harden blades, 2 hours with carbon potential (CP) at 1.10% temperature at 860°C, and (3) 7 pieces of gas-carbonitriding harden blades, 2 hours with carbon potential at 1.10%, temperature at 880°C. The Micro Vicker hardness test (HMV) was applied to measure the hardness of the specimen. The hardness was measured every 0.1 mm for 12 points. The testing pieces with the highest surface hardness at 0.1 mm, using the hardening 2 hours, CP at 1.10%, temperature at 860°C and 880°C, had the hardness measure at 720 HV and 730 HV, respectively. Each blade must pass approximately 5 tons of organic fertilizer to test its wear resistance on the impact. The results of the research revealed that forging impact blades that had not been hardened had a wear 5 mm, and the impact blades that had been hardened by gas carbonitriding using hardening 2 hours, temperatures at 860°C and 880°C, had a wear of 1.3 mm and 0.5 mm, respectively.